Keragaman Jenis Ikan Arus Deras di Aliran Riam Banangar Kabupaten Landak - Ari Hepi Yanti, Marcel Alveri Adis, Tri Rima Setyawati, (Universitas Tanjungpura, 2014)
Aquatic ecosystem of high stream water has particular characteristics of the fish with certain adaptation pattern. This study aims to determine species of fish, their level of diversity and condition of environmental factors in the stream of Banangar waterfall. This research was conducted for 2 months from June to July 2014 using purposive random sampling.The research found 21 species from 9 families withhighest fish abundance was at location 2 and the lowest one at station 3.Fishes from family Cyprinidea were frequently found which consisted of Lobocheilos bo (FR = 10.35%) and Hampalabimaculata (FR = 6.90%). The highest index of species diversity at station 1 (0.741) and the lowest index at station 3 (0.537). The highest of dominance index was at station 3 (0.291) and lowest was at station 2 (0.221). The highest of evenness index was at station 1 (0.337) and lowest was at location 2 (0.233). Enviromental condition in the stream flow of Banangar waterfall support fish with temperature ranges 27-28 0 C, speed water flow 0.56-1.42 m/s, pH in the range 7-9, Dissolved oxygen in the range of 5-6 ppm, and CO2at 6 ppm.